Meniscus matrix morphological composition: age-dependent evaluation in a swine model (International Journal of Health, Animal Science and Food Safety, 2017)
Menisci are fibro-cartilaginous structures interposed between femoral condyle and tibial plateau, which have multiple functions in the stifle joint: act as shock absorbers, bear loaders and allow joint stability, congruity and lubrication (Sweigart et al., 2004; Proffen et al., 2012). It is well known that meniscal injuries lead to osteoarthritis and for these reasons, menisci are considered important target of investigation. Their important role in the knee wellness is only equalled by their deficiency in proper self-repairing.Nowadays, the gold standard technique is not just to remove the damaged meniscus, but to rebuild it or to replace it. For these reasons, studies are necessary to increase the knowledge about these small but essential structures (Streuli, 1999; Deponti et al., 2013). Composition and morphology are basic fundamental information for the development of engineered meniscal substitutes (Di Giancamillo et al., 2014). The analysis of the morphological, structural and biochemical changes, which occur during growth of the normal menisci, represent the goal of the present study. For this purpose, menisci from adult (7-month old), young (1-month old), and neonates (stillbirths) pigs were collected. Cellularity and glycosamiglycans (GAGs) deposition were evaluated by ELISA, while Collagen-1 and Collagen-2 were investigated by immunohistochemistry and Western blot analyses. Cellularity (P
Keywords: Meniscus; pig; matrix